Qian Mu's guoshi dagang: reflections on a modern Chinese conservative - Chang, Yuan (2024)
This paper examines the predicament of modern Chinese conservatism. I use the eminent historian Qian Mu (1895-1990) as an example to show that under the influence of modernity and in an effort to preserve tradition, a prominent conservative like Qian needed to “modernize” Chinese tradition so that it could be saved. I will examine Qian’s reconstruction of Chinese history, which was not just a reiteration of China’s past, but a new type of understanding of Chinese tradition influenced by modern Western concepts. By focusing on Qian’s most prominent work, Guoshi dagang, we can get a sense of the struggle of modern Chinese conservatives as they tried to fend off the detractors of Chinese tradition.